Spiritual health of students in government medical colleges of Kolkata and their coping skills in a crisis situation - Shibotosh Sen; Dipak Pal; Suprakas Hazra; Girish Kumar Pandey (Wolters Kluwer Medknow Publications, 2015)
Background: The status of spiritual health of the population of India at large including that of young medical undergraduates who are the caregivers of the future and its association, if any, with coping skills in crisis situations is yet to be explored. Objectives: To measure the spiritual health status of the study population, describe the coping skills used by them in crisis situations, identify the sociodemographic factors associated with their spiritual health, and to determine the association of spiritual health status of the study population and their coping skills. Materials and Methods: An institution-based cross-sectional study was performed among the third semester medical students in government medical colleges of Kolkata, West Bengal, India. The study was conducted among 362 medical students by the survey questionnaire method. The Spiritual Health Scale 2011 (SHS 2011) and the Brief COPE Scale were used to measure the spiritual health and coping status, respectively. Results: Of all the respondents, 75.7% had refined spiritual health. The mean spiritual health score of the female students was significantly higher than that of the males. Of all the students, 66.1% showed good coping scores. Of all the respondents, 86.2% and 24.5% had higher adaptive and maladaptive coping scores, respectively. Refined spiritual categories were seen more among those students whose fathers had higher education and whose families arranged rituals at their homes. The spiritual health, self-evolution, and self-actualization scores of the respondents were significantly related to the adaptive coping scores and the fathers' education. Conclusion: The coping skills and hence, the spiritual health of the medical students were greatly influenced by the education of the father and cultural factor(s) like arranging annual rituals at home.